2016
DOI: 10.5127/jep.052515
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Attention Biases in understanding the link between Behavioral Inhibition and Anxiety

Abstract: The current study aimed to extend the results of White et al. (2015) by examining the moderating role of attention biases at age 5 on the relations between Behavioral Inhibition (BI) during toddlerhood and anxiety symptoms at age 10. Children’s BI at 2 and 3 years of age was measured using laboratory assessments, and attention bias towards threat was assessed using a dot-probe task at age 5. Latent Class Analysis (LCA) was used to identify the probability for children’s membership in an anxiety class, which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…Thirteen of the 23 studies (57%) examined whether covariates differentially predicted class membership. Of those, three found that the classes had different antecedents (Basten et al, 2013; Nozadi et al, 2016; Sulik et al, 2017), one found that classes differentially predicted other outcomes (Fergusson et al, 2009), and eight found cross-sectional associations (van Lier et al, 2003a,b; Lanza, 2011; Basten et al, 2013; Bradshaw et al, 2015; Racz et al, 2015; Wall et al, 2016; Carey et al, 2017). All studies found that classes had differential relationships with at least one covariate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen of the 23 studies (57%) examined whether covariates differentially predicted class membership. Of those, three found that the classes had different antecedents (Basten et al, 2013; Nozadi et al, 2016; Sulik et al, 2017), one found that classes differentially predicted other outcomes (Fergusson et al, 2009), and eight found cross-sectional associations (van Lier et al, 2003a,b; Lanza, 2011; Basten et al, 2013; Bradshaw et al, 2015; Racz et al, 2015; Wall et al, 2016; Carey et al, 2017). All studies found that classes had differential relationships with at least one covariate.…”
Section: Resultsmentioning
confidence: 99%
“…All studies found that classes had differential relationships with at least one covariate. Four studies also identified some covariates that did not have different associations with class (van Lier et al, 2003b; Lanza, 2011; Nozadi et al, 2016; Wall et al, 2016). Overall, the results from these 13 studies indicate that LCA produced externally valid classes.…”
Section: Resultsmentioning
confidence: 99%
“…White et al (2017), for example, one of the few studies with longitudinal data on the link between attention to threat and anxiety in young children, showed an interaction between attention to threat, temperament, and anxiety at age 7, but no relation at age 5. In a related study, Nozadi et al (2016) found that attention to threat at age 5 moderated the link between temperament in toddlerhood and anxiety at age 10; in other words, temperament predicted anxiety only for children who showed attentional biases toward threat. Further, in a large-scale meta-analysis, Clauss and Blackford (2012) concluded that BI is one of the most prominent risk factors for developing anxiety and social anxiety specifically.…”
Section: Attention and Anxiety In The Context Of Other Risk Factorsmentioning
confidence: 94%
“…A significant difference between the chi-square values demonstrates that the regression coefficients significantly differ between males and females. Because children excluded from the dot-probe task due to poor accuracy performance were more likely to be males and had lower effortful control, the model controlled for performance accuracy during the dot-probe task as in previous studies with this sample (Nozadi et al, 2016; White et al, 2017). Finally, preliminary analyses suggested that maternal education, r = .17, p = .018, and maternal ethnicity, r pb = .21, p = .003, were related to effortful control at age 4, such that children of mothers with higher levels of education and children of non-Hispanic Caucasian mothers had higher levels of effortful control.…”
Section: Methodsmentioning
confidence: 99%